Multimodal argumentation in digital media - Aquino, Zilda Gaspar Oliveira de (2021)
The purpose of this paper is to understand the structure of multimodal texts that are presented in digital media, especially Facebook, regarding the argumentative orientation they present. The method used is qualitative and the categories of analysis correspond to verbal elements that lead to the qualification or disqualification of referents that often involve the construction and deconstruction of frames - and to the visual elements, like the given and the new, that, used strategically in the construction of referents, promote the persuasion of interlocutors. Theoretically, we based ourselves on Perelman and Olbrechts-Tyteca (1996 [1958]), among others, regarding Argumentation Theories and proceeded to the correlation with Visual Semiotics, considering the positions of Kress and van Leeuwen (2001) on the concept of multimodality, in order to understand how the argumentative dimension materializes in a multimodal text. We understand with Silva and Marchon (2021) the occurrence of multimodal argumentation in texts produced from more than one modality (verbal and imagetic) that form a cohesive whole, to achieve the persuasion of the interlocutor. The selected corpus consists of five Facebook posts from the period of 2018 presidencial elections in Brazil. The results corroborate the defended thesis, highlighting, however, that nuances may occur regarding the diversified positions of the interlocutors facing this structure that we call multimodal argumentation